A 32-year-old man with hematuria and hemoptysis - Boonyakrai, Chanchana; Pakhakorntanatorn, Arpakorn; Leelasiri, Kulachon​; Thavarungkul, Paninee (Journal of the Nephrology Society of Thailand, 2022)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis is a systemic small-vessel vasculitis that can affect several organs including kidneys, respiratory tract and nervous system. It is also the most common cause of rapidly progressive glomerulonephritis in adults. The following case presentation is an adult male who presented with gross hematuria, hemoptysis and hypertension. His chest radiograph showed reticular infiltration. Interstitial pneumonitis and alveolar hemorrhage were observed in the pathology of lung tissue. Kidney biopsy revealed crescentic glomerulonephritis without endocapillary hypercellularity. Only focal staining (1+ to 2+) of IgG and fibrinogen was observed in the necrotic segments. He was diagnosed with granulomatosis with polyangiitis. He received pulse methylprednisolone followed by oral prednisolone and cyclophosphamide. The maintenance immunosuppression were prednisolone and azathioprine. He achieved a remission, and all immunosuppression was eventually discontinued.